2005
DOI: 10.1161/01.str.0000185932.73486.7a
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Susceptibility Vessel Sign on T2*-Weighted Gradient Echo Imaging for Identification of Stroke Subtypes

Abstract: Background and Purpose-In contrast to platelet-rich white thrombi, red thrombi in the heart are rich in fibrin and trapped erythrocytes. The magnetic susceptibility effect of deoxygenated hemoglobin in red thrombi may result in hypointense signals on T2*-weighted gradient echo imaging (GRE). We tested the hypothesis that a GRE susceptibility vessel sign (SVS) is specific for cardioembolic stroke. Methods-This retrospective study examined data from acute ischemic stroke patients who underwent diffusion-weighted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
196
8
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 195 publications
(223 citation statements)
references
References 16 publications
16
196
8
3
Order By: Relevance
“…In this study, clots with a GRE SVS showed significantly lower IL‐1 β , TNF‐ α and MMP‐9 expression compared to clots without an SVS. These results support the idea that a GRE SVS is more frequently observed in patients with cardiogenic embolic stroke than in those with other stroke subtypes3, 12 and clots with a negative SVS could be associated with atherosclerosis 3, 13. The T2‐shortening effect of the intracellular deoxyhemoglobin component in red blood cells within the clot is the pathophysiologic basis of an SVS 3.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…In this study, clots with a GRE SVS showed significantly lower IL‐1 β , TNF‐ α and MMP‐9 expression compared to clots without an SVS. These results support the idea that a GRE SVS is more frequently observed in patients with cardiogenic embolic stroke than in those with other stroke subtypes3, 12 and clots with a negative SVS could be associated with atherosclerosis 3, 13. The T2‐shortening effect of the intracellular deoxyhemoglobin component in red blood cells within the clot is the pathophysiologic basis of an SVS 3.…”
Section: Discussionsupporting
confidence: 82%
“…Paramagnetic intracellular deoxyhemoglobin leads to a nonuniform magnetic field causing marked signal loss on the GRE sequence because of spin dephasing. It was previously established that the presence of an SVS on GRE imaging was markedly associated with a higher red blood cell count in the clot, whereas fibrin‐dominant clots were associated with the absence of an SVS 3, 12. Fibrin‐dominant clots are typically formed because of endothelium injury overlies the complicated plaque in the setting of advanced atherosclerosis 13.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cho et al 33 found an association between pretreatment T2*-weighted gradient echo imaging-susceptibility vessel sign and subsequent recanalization in patients with large vessel occlusion; the assumption is that gradient echo imaging-susceptibility vessel sign predicts cardioembolic stroke and indicates fibrin-rich thrombi. In a post hoc analysis of this cohort, we rated the presence of gradient echo imaging-susceptibility vessel sign in patients with large vessel occlusion (N=66); 28% had gradient echo imaging-susceptibility vessel sign but we found no association with smoking status, stroke etiology, or subsequent recanalization.…”
Section: February 2013mentioning
confidence: 99%
“…4,5 The pathophysiologic basis for this sign in patients with an acute MCA occlusion is a T2-shortening effect of the intracellular deoxyhemoglobin component in erythrocytes within the clot. 4 Several researchers showed that the SVS was more commonly seen in red blood cell-dominant and mixed clots than in fibrin-dominant clots and could therefore reflect the composition of the clots.…”
mentioning
confidence: 99%